ANALYSIS Of CAPITAL ASSET PRICING MODEL ACCORDING TO SHARIAH PRINCIPLE: INDONESIAN EVIDENCE - Yuni Pristiwati Noer Widianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Capital Asset Pricing Model (CAPM) is one of the estimated return models developed in conventional financial instruments that have different characteristics from Islamic financial instruments. So the CAPM model cannot be directly applied in Islamic financial instruments, so an estimation model is needed, namely the Shariah Compliant Capital Asset Pricing Model (SCAPM). This study aims to produce a SCAPM model that can be applied to estimate returns in Islamic financial instruments. The data used in the test is a list of sharia companies listed on the IDX, sharia company stock prices, Indonesia Sharia Stock Index (ISSI), yield of sukuk and return of Bank Indonesia Certificates (SBI) for the period 2010 - 2018. Testing is done by comparing expected return with the CAPM and SCAPM models. The SCAPM model used is to eliminate the risk free asset factor and replace it with inflation, zakat, and yield of sukuk. The results of the analysis using graphs and the compare mean test show that the results of the expected return with the SCAPM and CAPM models have no difference, so the SCAPM model can be used as an alternative model of return estimation in Islamic Financial Instruments on the IDX.